Deploying Production-Grade Kubernetes Cluster - Kjorveziroski, Vojdan; Ribarski, Panche (My University, 2019)
Deploying a production-grade Kubernetes cluster is a challenging feat, mainly because of all the different services that need to be integrated with each other. We examined Kubespray, which is an open-source project whose purpose is to automate the deployment of stable clusters, as well as ease the future administration and lifecycle management along the way. Additional components can be installed during the deployment process that enrich and improve the cluster capabilities. We used Kubespray and together with other open-sources projects we created production-grade Kubernetes cluster ready for real deployment scenarios.
Keywords: Kubernetes; K8s; Docker; Kubespray; Helm; ELK; Monitoring; Automation; Containers; Orchestration